2021
DOI: 10.1177/19322968211054520
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Albumin-to-Creatinine Ratio Point-of-Care Testing on the Diagnosis and Management of Diabetic Kidney Disease

Abstract: Background: For the diagnosis of diabetic kidney disease (DKD), quantitative albuminuria measurement using the albumin-to-creatinine ratio (ACR) is recommended according to various guidelines. It can be measured either in specialized laboratories or using ACR point-of-care testing (POCT). This observational study aims at evaluating the effect of ACR POCT utilization on the DKD diagnosis and treatment management for glycemic control and blood pressure. Method: Data of 717 patients with diabetes (type 1 diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Nevertheless, a survey of primary care professionals in Europe [ 76 ] found that only 32.4% were fully confident in interpreting UACR results. Currently, UACR can also be determined by point-of-care testing (POCT) [ 77 ]. The survey also revealed that there is an unmet need for more information on screening, detection, and management of CKD [ 76 ].…”
Section: Key Topics Discussed During the 9th Cvot Summitmentioning
confidence: 99%
“…Nevertheless, a survey of primary care professionals in Europe [ 76 ] found that only 32.4% were fully confident in interpreting UACR results. Currently, UACR can also be determined by point-of-care testing (POCT) [ 77 ]. The survey also revealed that there is an unmet need for more information on screening, detection, and management of CKD [ 76 ].…”
Section: Key Topics Discussed During the 9th Cvot Summitmentioning
confidence: 99%
“…A change of medication based on the UACR POCT was performed in 21.6% of individuals with T2D and mostly in those with a severely increased UACR of >30 mg/ mmol. The majority of physicians involved in the study regarded UACR POCT as very important for people with diabetes (75%) and important for individuals without diabetes (75%) [53]. Thus, POCT tools should be made available in primary care to improve diagnostic rates and quality of care.…”
Section: Albuminuria Assessmentmentioning
confidence: 99%